PENGGUNAAN PERMAINAN TEBAK KATA DALAM MENINGKATKAN PENGUASAAN MUFRADAT BAHASA ARAB DI MA DARUL HIKMAH SONCOLELA - Gusdur, Gusdur; Nurlaila, Nurlaila; Nurdinawati, Nurdinawati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
In the Arabic language learning process, students still tend to sit listening, imitating, taking notes, and doing assignments in books only. There are some students who are still lacking in mastery of Arabic vocabulary because of the difficulty of memorizing and when the learning takes place, they pay less attention to the lessons presented, so that many chat by themselves with this, because students feel bored to take lessons because the learning system applied is still conventional. So in this study aims to describe the improvement of Mastery of Arabic Mufradat with the use of Guess the Word Game in class XI-A at MA Darul Hikmah Soncolela, Bima City, West Nusa Tenggara. The form of research is Classroom Action Research. The research place took place at MA Darul Hikmah Soncolela, the research subjects were class XI-A students totaling 20 students. The data collection techniques used are observation techniques, questionnaires, and documentation. The tools used are Questionnaire sheets, Observation sheets and students' Mufradat Mastery. Data analysis used is validity test, reliability test and descriptive statistics. This research was conducted in 2 cycles with the final results of the research obtained, namely in cycle I worth an average of 7.05. In cycle II, the average value is 7.45. From the data obtained, it can be concluded that there is an increase in students' Mastery of Arabic Mufradat with the use of Word Guess Games.